Penegakan Sanksi Administratif terhadap Pengelolaan Sampah Rumah Tangga di Kabupaten Tanjung Jabung Timur Menurut Peraturan Daerah Nomor 20 Tahun 2013 - imam ansori (Jurnal Hukum Lex Generalis, 2024)
Household waste problems in Tanjung Jabung Timur Regency continue to escalate along with population growth and increasing community activities. The local government has issued Regional Regulation Number 20 of 2013, which regulates waste management obligations and the imposition of administrative sanctions for violations. This study aims to examine the implementation, obstacles, and mechanisms of administrative sanctions in household waste management. The method used is empirical juridical with a descriptive qualitative approach. Data were obtained through interviews and document studies. The results show that administrative sanctions have not been effectively enforced. The government prioritizes persuasive approaches, while sanctions such as warnings, government coercion, and license revocation have not been implemented. Major obstacles include low public awareness, inadequate waste facilities, and weak supervision. This study suggests strengthening the role of law enforcement officials, increasing legal education for the public, and consistent application of sanctions to ensure waste management complies with regulatory objectives.